Handbook of research on ethnic and intra-cultural marketing - Brodowsky, Glen H.; Schuster, Camille P.; Perren, Rebeca (Research handbooks in business and management series, 2022)
"Investigating how markets are becoming increasingly similar across countries while simultaneously becoming more diverse and heterogeneous within countries, this timely Handbook explores novel and under-researched sub-cultural marketing segments. Contributions from a diverse group of established and emerging marketing scholars examine how we might better understand and serve new generations of consumers from a variety of generational, ethnic, and religiously diverse market segments. Cognisant of the cultural diversity within cultures, the Handbook considers the ethical ramifications of culture- and race-based targeting and segmentation, advancing a culture-based marketing approach that addresses the similarities and differences across groups while recognising the variety that exists within them. Chapters explore a compelling array of topics, from advocating for a departure from the white, Eurocentric, and heteronormative ideals that dominate the global beauty industry and investigating how Hip Hop's move into the mainstream raises questions about authenticity and cultural appropriation, to addressing the role played by religion in consumer behaviour and mapping the diverse and complex markets of Latin America and Asia. Featuring multidisciplinary research which builds towards a more vibrant ethnic and sub-cultural marketing literature, this compelling Handbook will inform and inspire the work of current and future marketing scholars. It will also be an essential resource for corporations interested in targeting ethnic and religious marketing segments"--